Educating in An Era of Distortion: Effective Literacy as The Foundation of Education Amidst An Information Explosion - Arman Paramansyah (Journal of Pedagogi, 2025)
The digital era has generated an unprecedented explosion of information that exposes students to misinformation, algorithmic bias, and distorted narratives, thereby challenging the traditional functions of education. This study positions information literacy not as a technical skill but as a foundational cognitive, social, and ethical capacity required to navigate an increasingly volatile and manipulative digital ecosystem. Using a descriptive qualitative method based on literature analysis, this research synthesizes scholarly perspectives from recent studies on information literacy, digital citizenship, educational epistemology, and post-pandemic learning dynamics. Data were analyzed through content reduction, thematic identification, and conceptual synthesis to map how literacy operates as an epistemic safeguard. The findings indicate that literacy equips learners with the capacity to evaluate, verify, and reconstruct information, enabling them to resist hoaxes, polarization, and emotionally driven misinformation. Literacy also strengthens moral judgment, social responsibility, and collaborative knowledge construction, forming an educational security system that protects against information distortion. However, the study identifies persistent barriers, including memorization-oriented evaluation systems, limited educator readiness, emotional dependence on digital spaces, and cultural tendencies toward opinion-based truth. These obstacles hinder literacy from functioning effectively as the foundation of contemporary education. The conclusion emphasizes that literacy must be redefined as an existential educational core that sustains critical thinking, ethical reasoning, and citizenship in an era of informational instability. By reconceptualizing literacy in this way, the information explosion becomes an opportunity to cultivate intellectually autonomous and socially responsible learners.